Risk Factors for Periprosthetic Joint Infection - جوني, أحمد; علي, ناظم; أحمد, محي الدين (Latakia University Journal -Medical Sciences Series, 2021)
Periprosthetic joint infection is one of the most challenging complications of joint arthroplasty. We identified current risk factors of periprosthetic joint infection after modern joint arthroplasty, and determined the incidence and timing of periprosthetic joint infection. We reviewed prospectively collected data from our database on 221 patients (80 males and 141 females) undergoing primary hip or knee arthroplasty between the year 2018 to 2019.They aged between (31-97 years old) and we have 189 patient undergoing hip arthroplasty and 32 patient undergoing knee arthroplasty. Periprosthetic joint infections developed in 24 patients (10,9%). (83,3%) of periprosthetic joint infections developed within the first three months of the index arthroplasty. The most common organisms identified were Staphylococcus aureus in (33,33%) of cases. We identified the following independent predictors for periprosthetic joint infection: smoking, alcohol abuse, allogeneic transfusion, postoperative atrial fibrillation, uncontrolled diabetic, preoperative anemia, chronic renal failure, BMI>30kg/m2, systemic steroid therapy, distant infection, length of operative (>120min), longer hospital stay, longer wound draing, non-same day surgery.